The need of independent shariah members in Islamic cooperative banks: an empirical study of professional accountants in Malaysia - Ahmad, Mohd Rodzi; Al-Aidaros, Al-Hasan (Academy of IRMBR, 2015)
The importance of shariah members in Islamic financial institutions, in some of its aspects, is to audit and check the financial system in accordance to Islam.Thus, independence status of auditor is complement to the shariah members to function effectively.To be independence shariah auditor, there is need to have separation of duties between shariah auditors and Shariah Committee to perform their duties.The purpose of this study is to assess the importance of the independent of the shariah members in Islamic Cooperative Banks in Malaysia.The methodology adopted in this study is limited to questionnaires distributed to 50 professional accountants in Malaysia.Data were analyzed using descriptive analysis.The results proved that fifty two percent of shariah auditors had total independence and played important role in ensuring shariah compliant of products and activities and their practices have been well accepted by stakeholders of Islamic Cooperative Banks.Moreover, sixty seven percent shariah auditors have been given a free reign to perform their functions and were free from intervention by the Shariah Committee during the audit process.However, shariah auditors have less team members to perform their audit services. Furthermore, most shariah auditors agree that there is a lack of expertise or human talent to perform these sorts of audit services currently in Malaysia. Finally, this study has shown that most auditors agree that there is a need to enhance their knowledge and expertise in shariah auditing in order to improve and master shariah accounting and auditing processes.